The effects of a professional development programme on primary school teachers' perceptions of physical education - Jo Harris; Lorraine Cale; Hayley Musson (2011)
The impact of a professional development programme on primary school teachers’ perceptions of physical education was investigated. Primary school teachers from five local education authorities in England provided data for the study via pre‐course audits, course evaluations immediately following the programme, and focus groups and individual interviews up to 18 months after the programme. The programme was considered by the teachers to have positively affected their perceptions of physical education (in terms of their confidence in, knowledge of and enthusiasm for the subject) and, in turn, improved their practice (particularly in terms of content ideas and inclusion). Key limitations of the programme were identified as insufficient attention to specific pedagogical issues (such as medium to long‐term planning and assessment) and the absence of follow‐up support. In conclusion, the programme positively contributed to teachers’ perceptions of physical education; however, beyond this, its impact was limited by a range of factors.